Efektivitas ShopeePay sebagai Alat Pengelolaan Keuangan dan Strategi Pemasaran bagi UMKM Makanan - Mungawanah, Ngaliyatul; Yuliamir, Henry (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to analyze the effectiveness of using ShopeePay in financial management and marketing strategies for food MSMEs in Semarang City. The main focus of this study is to understand the extent to which ShopeePay affects the transparency and efficiency of financial recording and its contribution to increasing the number of customers through the digital promotion features provided. This study uses a qualitative approach with a theoretical basis regarding digital payment systems, digital marketing, and consumer behavior in online transactions. Data were collected through in-depth interviews with food MSME owners who use ShopeePay and participant observation of the transaction process. The results of the study show that ShopeePay helps business actors record transactions more systematically and transparently, reduces the risk of inaccurate recording or cash leakage, and facilitates daily cash flow management. From a marketing perspective, cashback programs, discounts, and loyalty systems such as Shopee Coins have been shown to increase the number of customers and strengthen consumer retention. However, there are a number of obstacles that hinder the optimization of ShopeePay, including limited balances on customer e-wallets that reduce the frequency of purchases, as well as the lack of understanding of MSME owners in operating available digital marketing features, which has an impact on the low effectiveness of promotions. This study contributes to the development of literature in the field of digital finance and MSME marketing, especially in the Indonesian context, by filling the gap regarding the impact of digital payment systems on the operational and marketing performance of MSMEs in the food sector. These findings also form the basis for efforts to improve digital literacy and more targeted technology training for MSME actors.